Mesoscale and Submesoscale Effects on Mixed Layer Depth in the Southern Ocean - Bachman, SD; Taylor, JR; Adams, KA; Hosegood, P (American Meteorological Society, 2017)
Submesoscale dynamics play a key role in setting the stratification of the ocean surface mixed layer and mediating air–sea exchange, making them especially relevant to anthropogenic carbon uptake and primary productivity in the Southern Ocean. In this paper, a series of offline-nested numerical simulations is used to study submesoscale flow in the Drake Passage and Scotia Sea regions of the Southern Ocean. These simulations are initialized from an ocean state estimate for late April 2015, with the intent to simulate features observed during the Surface Mixed Layer at Submesoscales (SMILES) research cruise, which occurred at that time and location. The nested models are downscaled from the original state estimate resolution of 1/12° and grid spacing of about 8 km, culminating in a submesoscale-resolving model with a resolution of 1/192° and grid spacing of about 500 m. The submesoscale eddy field is found to be highly spatially variable, with pronounced hot spots of submesoscale activity. These areas of high submesoscale activity correspond to a significant difference in the 30-day average mixed layer depth ΔH_ML between the 1/12° and 1/192° simulations. Regions of large vertical velocities in the mixed layer correspond with high mesoscale strain rather than large ΔH_ML. It is found that ΔH_ML is well correlated with the mesoscale density gradient but weakly correlated with both the mesoscale kinetic energy and strain. This has implications for the development of submesoscale eddy parameterizations that are sensitive to the character of the large-scale flow. The authors gratefully acknowledge support from the Natural Environment Research Council Awards NE/J010472/1 and NE/J009857/1.